Efficacy and safety of tirzepatide in patients with type 2 diabetes mellitus: A bayesian network meta-analysis - Guan, Ruifang; Yang, Qing; Yang, Xiaolei; Du, Wandi; Li, Xuening; Ma, Guo (Frontiers in Pharmacology, 2022)
Background: In light of clinical trials comparing different doses of tirzepatide with selective glucagon-like peptide-1 receptor agonist (GLP1-RA) or insulin analogue, a bayesian network meta-analysis was conducted to investigate the efficacy and safety of tirzepatide in patients with type 2 diabetes mellitus (T2DM). Methods: We systematically searched PubMed, Embase, Web of science, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov from their inception to 2 May, 2022. Final included studies met the eligibility criteria and methodological quality recommendations. Data analysis was performed using Stata 15.1 software. Each outcome was presented as a mean difference or an odds ratio, and the surface under the cumulative ranking curve value (SCURA). Results: Ultimately, 8 eligible RCTs involving 7245 patients were included. Generally speaking, compared with basal insulin (glargine or degludec); selective GLP1-RA (dulaglutide or semaglutide once weekly), 10 and 15 mg of tirzepatide exhibited better antidiabetic and weight-loss effect, especially, 15 mg of tirzepatide was dominant on reducing glycated hemoglobin (SCURA probability: 93.5%), body weight (99.7%), and fasting serum glucose (86.6%). As for safety, insulin caused less gastrointestinal events (93.5%), and there was no statistical difference between GLP1-RA and tirzepatide. Conclusions: Compare with insulin and GLP1-RA, tirzepatide display favorable efficacy and acceptable safety for T2DM patients. More well-designed RCTs are needed to evaluate its clinical performance with higher doses of GLP1-RA and determine its potential cardiovascular benefits.